Atenção primária à saúde e oftalmologia: percepção discente sobre a aquisição de competências na formação médica - Biase, Carmem Lúcia Carneiro Leão De (2017)
One of the greatest challenges faced by medical schools in Brazilian universities is to educate a generalist, critical, reflective, humanist, and resolute professional, who operate appropriately in primary health care (PHC). In this context the present study aims to evaluate the skills and students perception of undergraduate medical interns from Federal University of Alagoas (UFAL), regarding their training in ophthalmology in PHC. It is a case study, where the data was obtained by performing an OSCE (objective clinical structured examination) and through the thematic analysis of students' answers to two open questions about their training in ophthalmology in PHC. Results showed that despite the present subjects presented an education in ophthalmology care in PHC, this formation is not arising exclusively from the discipline of ophthalmology and eye care knowledge throughout the course are due to other present moments in the formal curriculum. This work resulted in two intervention products: the introduction of a practical class in the discipline of ophthalmology for medical students with frequent themes in primary health care (PHC) and a technical report on the objectives and results of the research presented to the Structural Teaching Nucleus (STN) the UFAL Medicine Course.